The Dual Role of the Immune Response in Reproductive Organs During Zika Virus Infection - Arévalo Romero, Haruki; Vargas Pavía, Tania A.; Velázquez Cervantes, Manuel A.; Flores Pliego, Arturo; Helguera Repetto, Addy C.; León Juárez, Moises (Frontiers in Immunology, 2019)
Zika virus is a mosquito-borne viral disease that emerged as a significant health problem in the Americas after an epidemic in 2015. Especially concerning are cases where Zika is linked to the development of brain abnormalities in newborns. Unlike other flaviviruses, Zika can be transmitted sexually, increasing the potential for intraspecies infection. Several reports show that the virus can persist for months in the testis of males after clearance of viremia, and that females are highly susceptible to infection via sexual transmission. The most common route of sexual transmission is male-to-female, which suggests that the mechanism driving persistence of Zika in the testis is essential for dissemination. The immune system plays an essential role in Zika infection. In females a robust response inhibits the virus to control the infection. In males, however, the immunological response to Zika infection correlates with viral persistence. Thus, the immune system may have a dual role in sexually transmitted pathogenesis. The mechanism by which the immune system allows the virus to enter an immune-privileged site while continuing to disseminate is unclear. In this mini-review, we highlight advances in our knowledge of sexually transmitted Zika virus pathogenesis and the possible mechanisms mounted by the immune system that control or exacerbate the infection.